Synthesis of large gold nanoparticles with deformation twinnings by one-step seeded growth with Cu(ii)-mediated Ostwald ripening for determining nitrile and isonitrile groups. Issue 32 (10th August 2020) - Wu, Chenshuo; He, Hongpeng; Song, Yahui; Bi, Cuixia; Xing, Lixiang; Du, Wei; Li, Shenggang; Xia, Haibing
Abstract : Gold nanoparticles with deformation twinnings prepared by a Cu 2+ -assisted one-step seeded growth method can distinguish nitrile and isonitrile groups by SERS. Abstract : In this work, uniform and large gold nanoparticles (Au NPs) including quasi-spherical (QS) Au NPs with average diameters of 70 to 196 nm and trisoctahedral (TOH) Au NPs with average diameters of 140 to 195 nm were successfully synthesized by controlling the concentration of Cu 2+ ions and the particle number of 3 nm Au-NP seeds, respectively, using a one-step seeded growth method with Cu 2+ -mediated Ostwald ripening. It is found that because of the concentration-dependent under-potential deposition of Cu 2+ ions (CuUPD ), 3 nm Au-NP seeds are firstly changed into Au NPs with a controlled QS- or TOH shape at the initial growth stage, followed by the conformal growth of Au atoms onto the initially formed Au NPs due to Cu 2+ -mediated Ostwald ripening, in which the extra Au atoms come from the dissolution of in situ Au nuclei by the unavoidable self-nucleation. Moreover, the as-prepared QS Au NPs with a rough surface exhibit a better SERS performance for physically adsorbed probes (crystal violet, CV) than the TOH Au NPs with sharp tips and with a comparable size. Furthermore, the as-prepared QS Au NPs can be used to distinguish nitrile and isonitrile groups by surface-enhanced Raman scattering (SERS) due to the presence of deformation twinnings. Thus, the as-prepared QS Au NPs with a rough surface and deformation twinnings can be further used as templates for the fabrication of bimetallic materials with multi-functionalities.